2010
DOI: 10.1097/mao.0b013e3181cabd77
|View full text |Cite
|
Sign up to set email alerts
|

Intractable Benign Paroxysmal Positioning Vertigo

Abstract: The low incidence of nystagmus transition in patients with apogeotropic nystagmus suggests a difference in pathophysiology between apogeotropic nystagmus and other types of BPPV. Stenosis and filling defect (obturation) of canals on MRI, which would indicate an innate narrowing and/or an otoconial jam of the semicircular canal, may account for the intractability of BPPV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(9 citation statements)
references
References 13 publications
0
7
0
2
Order By: Relevance
“…Accordingly, the innate stenosis of the canal could induce an otoconial debris jam in the narrow portion, although a giant otoconial plug could occur in a normal canal. Horii et al [5] recently suggested that patients with intractable BPPV had more abnormal appearing canals compared with normal controls based on 3-dimensional reconstruction of inner ear MR images.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the innate stenosis of the canal could induce an otoconial debris jam in the narrow portion, although a giant otoconial plug could occur in a normal canal. Horii et al [5] recently suggested that patients with intractable BPPV had more abnormal appearing canals compared with normal controls based on 3-dimensional reconstruction of inner ear MR images.…”
Section: Discussionmentioning
confidence: 99%
“…В то же время отсутствие эффекта от маневров должно насторожить врача в плане правильности диагноза. В некоторых случаях низкая эффективность маневров связана с аномалией развития полукружных каналов, для диагностики которой используется магнитно-резонансная томография (МРТ) [51]. Низкая эффективность лечебных маневров может быть связана с адгезией отоконий в канале или купуле.…”
Section: атипичные варианты дппгunclassified
“…Encouraging advances in imaging may eventually enable in vivo correlation. Three-dimensional T2-weighted 3-dimensional fast MRI imaging with steady-state acquisition sequences can now show some reliable detail of semicircular structure such as narrowed areas and “filling defects” [82]. In patients with “intractable” BPPV 89% had abnormal canals compared with healthy controls, but there was no correlation between the affected canal and nystagmus type.…”
Section: Future Directionsmentioning
confidence: 99%